EFFECTIVENESS OF AIR TRAFFIC CONTROL IN UNRELIABLE CHANNELS OF INFORMATION EXCHANGE BETWEEN AIR TRAFFIC CONTROLLERS AND FLIGHT CREW - E. G. Unichenko (Научный вестник МГТУ ГА)
The article considers the possibility of dangerous approaches of aircraft and the magnitude of risk of collision with the direct ATC.